Identification of novel proteins associated with the development of chemoresistance in malignant melanoma using two-dimensional electrophoresis - Sinha-von Jaschke, Pranav; Kern, Monika; Schnölzer, Martina; Schadendorf, Dirk (Electrophoresis, 2000)
A model system for studying chemoresistance in human melanoma cells (MeWo) has been established utilizing the four commonly used cytotoxic drugs vindesine, cisplatin, fotemustine and etoposide to yield stable drug-resistant sublines. We analyzed phenotypical differences between MeWo cells and their chemoresistant counterparts using two-dimensional electrophoresis. Proteins that were overexpressed in chemoresistant cell lines were purified and identified using matrix assisted laser desorption/ionization-time of flight — mass spectrometry (MALDI-TOF-MS) and microsequencing. Here we show that four proteins, namely the translationally controlled tumor protein, the human elongation factor 1-δ, tetratricopeptide repeat protein and the isoform 14-3-3-γ of the 14-3-3-family are overexpressed in chemoresistant melanoma cell lines. The significance of these findings is now being verified using transfection experiments with the aim of developing more effective chemotherapy protocols.
Gesehen am 26.02.2019